The Distorted Speech Vocalisms Harmonic Structure Restoration by means of Dynamic Spectrograms Images Digital Processing - Victor Mikhailovich Alyushin; Sergey Vladimirovich Dvoryankin (Безопасность информационных технологий, 2013)
The harmonic structure of noisy speech reconstruction method based on pitch and divisible harmonies frequency determination on vocalized sections along spectral-time descriptions images is presented in this work. The main tone frequency calculation algorithm utilizing parabolas tops on current spectral dissections slices is examined. The results obtained may be used in solving problems of speech recovery from noises and disturbers, synthesis and coding sound signals and automatic speaker identification.